C57BL/6 substrain differences in inflammatory and neuropathic nociception and genetic mapping of a major quantitative trait locus underlying acute thermal nociception. (February 2019) - Bryant, Camron D; Bagdas, Deniz; Goldberg, Lisa R; Khalefa, Tala; Reed, Eric R; Kirkpatrick, Stacey L; Kelliher, Julia C; Chen, Melanie M; Johnson, William E; Mulligan, Megan K; Imad Damaj, M
Sensitivity to different pain modalities has a genetic basis that remains largely unknown. Employing closely related inbred mouse substrains can facilitate gene mapping of nociceptive behaviors in preclinical pain models. We previously reported enhanced sensitivity to acute thermal nociception in C57BL/6J (B6J ) versus C57BL/6N (B6N ) substrains. Here, we expanded on nociceptive phenotypes and observed an increase in formalin-induced inflammatory nociceptive behaviors and paw diameter in B6J versus B6N mice (Charles River Laboratories). No strain differences were observed in mechanical or thermal hypersensitivity or in edema following the Complete Freund's Adjuvant model of inflammatory pain, indicating specificity in the inflammatory nociceptive stimulus. In the chronic constrictive nerve injury, a model of neuropathic pain, no strain differences were observed in baseline mechanical threshold or in mechanical hypersensitivity up to one month post-chronic constrictive nerve injury. We replicated the enhanced thermal nociception in the 52.5°C hot plate test in B6J versus B6N mice from The Jackson Laboratory. Using a B6J × B6N-F2 cross (N = 164), we mapped a major quantitative trait locus underlying hot plate sensitivity to chromosome 7 that peaked at 26 Mb (log of the odds [LOD] = 3.81, p < 0.01; 8.74 Mb-36.50 Mb) that was more pronounced in males. Genes containing expression quantitative trait loci associated with the peak nociceptive marker that are implicated in pain and inflammation include Ryr1, Cyp2a5, Pou2f2, Clip3, Sirt2, Actn4, and Ltbp4 (false discovery rate < 0.05). Future studies involving positional cloning and gene editing will determine the quantitative trait gene(s) and potential pleiotropy of this locus across pain modalities.